Serological survey of Aujeszkys disease in Peninsular Malaysia in 2016 - Low, Suet Ee; Peck, Toung Ooi; Abdul Rahaman, Yasmin; Tan, Sheau Wei; Zi, Herk Cheah; Heng, Eric Chow Cheah; Pei, Evonne Qin Lim; Chiun, Khang Yong; Kok, Yen Kam (Nexus Academic Publishers, 2018)
Aujeszky’s disease (AD) is a common swine disease that widespread throughout the world. The symptoms include nervous signs, respiration and reproduction problems that lead to great economic losses to the industry. AD is endemic in Malaysia, where outbreaks had been reported in previous years. In Malaysia, approximately 95% of the pig farms are vaccinated for AD. Despite the regular vaccination, AD serological status remains unknown in this country. This study provides AD serological status in Peninsular Malaysia in 2016 based on the samples submitted to Faculty of Veterinary Medicine, University Putra Malaysia (UPM). A total of 1154 serum samples from 36 farms were submitted for AD ELISA diagnostic test; grouped as 8 weeks, 12 weeks, 16 weeks, 20 weeks, gilts and sows with different parity. The samples were subjected to AD antibody detection with IDEXX Pseudorabies Virus gpI Antibody Test Kit. Among the 36 farms submitted to UPM, 8 farms were detected with positive gI antibody indicated that these farms were still facing challenges from AD field virus. Among these eight seropositive farms, three farms were having seroprevalence in the range of 33.33% to 37.14%. In general, vaccination of AD is ideal and stable in Malaysia but we still need to be alert with the field challenge as it will be a threat to the industry.